2021
DOI: 10.1088/1742-6596/1793/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Digital Games in Advancing Students’ Higher-Order Thinking Skills: A Review

Abstract: The 4.0 industrial revolution transformed life remarkably. Dependence on technology is notable and influences the learning system in our country. In fact, its weight becomes more visible in the post-COVID-19 situation that strikes the world today. Online learning compels educators to be more creative in designing the learning process. One of them is to employ a digital game strategy in learning that utilises the elements of the game intending to motivate students, maximise positive feelings and engagement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Recent studies shown that digital game is effective in developing 21st century skills including HOTS either in Malaysia or out of Malaysia [36]. Besides, digital games also influence attitude toward learning in positive magnitude and it would affect their learning performance [37], [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies shown that digital game is effective in developing 21st century skills including HOTS either in Malaysia or out of Malaysia [36]. Besides, digital games also influence attitude toward learning in positive magnitude and it would affect their learning performance [37], [38].…”
Section: Discussionmentioning
confidence: 99%
“…Implementing this idea is a complex task. In today's information age, dependency on technology is notable and influences the learning system [2], the 4th industrial revolution, past the COVID-19 era, remarkably transformed the way we live and learn. Game learning compels creative learning, motivates students, and provides opportunities to explore innovative content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To challenge participants to identify and investigate diverse use of pedagogical agents as learning tools across disciplines, the researcher modeled five core instructional practices. The modeling practices included positioning teachers as designers with the use of pedagogical agents [48]; exploring higher-order thinking tasks to rethink the use of pedagogical agents [49]; developing problemsolving and research skills to enhance understanding; engaging learners in collaborative learning [50]; and conducting formative, summative, as well as pre-assessment assessments [51].…”
Section: Utilize Pedagogical Agents To Conduct Formative Assessmentsmentioning
confidence: 99%